Array-aided CORS network ambiguity resolution - Li, Bofeng; Teunissen, Peter (Springer, 2014)
Array-aided precise point positioning (A-PPP) is a measurement concept that uses Global Navigation Satellite System (GNSS) data, from multiple antennas in an array of known geometry, to realize the improved GNSS parameter estimation. In this contribution the ambiguity resolution benefits of A-PPP for antenna-array equipped CORS stations is explored. To demonstrate the performance of array-aided ambiguity resolution between station, an 80 km baseline experiment, equipped with a 6-antenna array at each CORS station, was conducted. We formulate the underlying model, show how the array-data to be reduced and present numerical results on the ambiguity resolution performance. The results show that the use of antenna-arrays can significantly improve the CORS network ambiguity resolution.